2004
DOI: 10.1097/01.mol.0000137222.23784.2a
|View full text |Cite
|
Sign up to set email alerts
|

Current management of severe homozygous hypercholesterolaemias

Abstract: Patients with severe homozygous hypercholesterolaemia illustrate the natural history of atherosclerosis within a condensed timeframe. Effective cholesterol-lowering treatment started in early childhood is essential to prevent onset of life-threatening atherosclerotic involvement of the aortic root and valve, and the coronary arteries. Noninvasive methods for regular monitoring of the major sites involved in the atherosclerotic process are necessary in patients with no symptoms or signs of ischaemia. Management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 93 publications
(77 reference statements)
0
49
0
3
Order By: Relevance
“…[92][93][94] These high plasma LDL-C levels lead to deposits of cholesterol in tendons, cutaneous tissues, and vasculature, including the coronary arteries, aortic root and valve, carotid arteries, and renal arteries. 95 Severe and widespread atherosclerosis occurs in all major arterial beds from a young age. 92,94 Untreated patients with homozygous FH who are LDL receptor negative (<2% residual of normal LDL receptor activity) rarely survive beyond the second decade.…”
Section: Natural History Of Homozygous Fh and Subclinical Atherosclermentioning
confidence: 99%
“…[92][93][94] These high plasma LDL-C levels lead to deposits of cholesterol in tendons, cutaneous tissues, and vasculature, including the coronary arteries, aortic root and valve, carotid arteries, and renal arteries. 95 Severe and widespread atherosclerosis occurs in all major arterial beds from a young age. 92,94 Untreated patients with homozygous FH who are LDL receptor negative (<2% residual of normal LDL receptor activity) rarely survive beyond the second decade.…”
Section: Natural History Of Homozygous Fh and Subclinical Atherosclermentioning
confidence: 99%
“…In the third pregnancy trimester, especially on delivery, high-intensity stress is added to the cardiovascular system; therefore, LDL apheresis should be performed during pregnancy. Several studies have reported that LDL apheresis therapy could be safely conducted during pregnancy, leading to delivery 72,84,85) . During lactation, lipid-lowering agents other than bile acid resins should also be discontinued, and periodic LDL apheresis therapy must be continued for LDL-C control.…”
Section: Drug Therapy For Homozygous Fhmentioning
confidence: 99%
“…Individuals with FH are at increased risk for cardiac events such as premature myocardial infarction and early death from premature coronary heart disease (CHD) especially in patients with severe forms of the disease if left untreated. 2,9,10 HeFH is characterized by 1 normally functioning gene and is less severe and more responsive to treatment such as statins than HoFH. The mean age for the onset of CVD in men with HeFH is 42 to 46 years and in women, onset is 51 to 52 years.…”
mentioning
confidence: 99%
“…11,12 HoFH is a severe, aggressive form of FH, which is often unresponsive to traditional treatment for hypercholesterolemia owing to the patient's lack of functional LDL receptors. 10,12 In patients with HoFH, the mean age at the time of diagnosis of CVD is 20 years. 3,[35][36][37] Risk stratification algorithms are often used to identify candidates for drug therapy on the basis of estimated CVD risk.…”
mentioning
confidence: 99%